1977
DOI: 10.1080/05698197708982832
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Plain Hydrodynamic Journal Bearings During Starting and Stopping

Abstract: The work described is concerned with the behavior of plain, hydrodynamic joulnal bearings during starting and stopping under a steady load.The starting behavior indicated that a rapid buildup of hydrodynamic forces occurred i n all cases. A hydrodynamic film was formed i n a very short time, after which the shaft moved in a spiral shaped whirling locus to the steady state operating position. Prior to separation of the shaft and bearing srcfaces, the contact was mainly a sliding situution with little or no init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 4 publications
3
19
0
1
Order By: Relevance
“…With increasing sliding speed, the effects of surface roughness on the transient characteristics of hydrodynamic cylindrical bearings become more prominent. In further simulation studies [21,25], it was shown that the time duration of asperity contact during startup can be reduced by lowering surface roughness, which is in agreement to experimental observations [26].…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…With increasing sliding speed, the effects of surface roughness on the transient characteristics of hydrodynamic cylindrical bearings become more prominent. In further simulation studies [21,25], it was shown that the time duration of asperity contact during startup can be reduced by lowering surface roughness, which is in agreement to experimental observations [26].…”
Section: Introductionsupporting
confidence: 85%
“…10(b). The slight increase of CoF can be explained by the negligible asperity interaction during stopping, which was also observed by Mokhtar et al [26].…”
Section: Comparison Of Simulated and Experimental Frictional Lossessupporting
confidence: 75%
See 2 more Smart Citations
“…In regard to mixed lubrication, Beheshti and Khonsari [21] focused on an elastohydrodynamic lubrication (EHL) line contact and presented an engineering approach for the prediction of wear under steady-state operation in the mixed lubrication regime by making use of the load-sharing concept and a modified Archard's wear law. Besides steady-state operation, journal bearings are also subjected to varying operation conditions, e.g., instabilities and starting and stopping [22]. The consideration of the dynamic state of operation is an important aspect within the numerical evaluation of journal bearings.…”
Section: Introductionmentioning
confidence: 99%